2014
DOI: 10.1002/j.2168-0159.2014.tb00089.x
|View full text |Cite
|
Sign up to set email alerts
|

25.3: A 9.55‐inch Flexible Top‐Emission AMOLED with a‐IGZO TFTs

Abstract: By using a-IGZO TFT backplane fabricated on polyimide foil, and top emission OLED structure, full color 9.55-inch flexible AMOLED display is developed. The process and the experiment results are introduced. The V th shift of a-IGZO TFTs was described before and after laser lift-off. The V th shift of a-IGZO TFT after 5,000 times bending test at 20mm curvature radius is less than 1.0V. We also introduce laser affections to the transfer characters of a-IGZO TFTs by different energies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…In the last few years, the increasing demand of flexible display has boosted large amount of research and development in flexible displays [1][2][3].The structure of a flexible AMOLED display can be divided into several parts: the flexible substrate, TFT backplane, OLED, and encapsulation layers. The AMOLED display contains functional brittle inorganic layers that have different purposes and could easily fail during bending [4].The stress of thin film is very sensitive for flexible substrate.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, the increasing demand of flexible display has boosted large amount of research and development in flexible displays [1][2][3].The structure of a flexible AMOLED display can be divided into several parts: the flexible substrate, TFT backplane, OLED, and encapsulation layers. The AMOLED display contains functional brittle inorganic layers that have different purposes and could easily fail during bending [4].The stress of thin film is very sensitive for flexible substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, organic light emitting diode (OLED) [1][2][3] is considered as one of the most promising display technology for their high efficiency, fast response, and wide viewing angels. OLED is sensitive to the environment so that encapsulation for OLED required high gas barrier properties.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many research groups have been reported that InGaZnO (IGZO) TFTs on polyimide plastic substrate have already obtained similar TFT performance such as electron mobility and I on /I off ratio, excellent uniformity, and good transparency compared to rigid substrates. 3,4 Most of the amorphous-IGZO based TFTs are still fabricated at relatively high process temperatures, typically above 300 C, to obtain the high quality gate insulator deposited chemical vapor deposition and the energy for activation for IGZO channel. This requires a thermally stable plastic substrate, e.g., polyimide, 1,5 which is expensive and has low optical transparency.…”
mentioning
confidence: 99%